44P Evaluation of immune response in young patients with sarcoma treated by dendritic cell-based immunotherapy. (15th December 2019) - Fedorova, L; Dubska, L Zdrazilova; Selingerova, I; Pilatova, K; Mudry, P; Sterba, J; Demlova, R; Valik, D
Abstract: Background: Individually prepared immunotherapy (ITx) based on autologous dendritic cells (DCs) represents a new possibility in modern advanced anti-cancer treatment. As an extended evaluation of DC-based medicinal product in an academic phase I/II clinical trial for children, adolescents and young adults with progressive, recurrent or primarily metastatic high-risk tumors (EudraCT 2014-003388-39), we performed the examination of T-cell stimulatory properties and detailed peripheral blood immunomonitoring. Methods: Ten patients (6 female, 4 male, median age 19 years) with relapsing sarcomas disease were treated with DCs pulsed with self-tumor antigens. DC ITx was administered intradermally in 2-4 week intervals. Peripheral blood was collected at baseline, after 5th, 9th and 13th dose. Nine circulating immune markers were quantified by flow cytometry: absolute lymphocyte count (ALC), neutrophil-to-lymphocyte ratio (NLR), effector CD8+T-cells, activated CD8+ T-cells, γδ T-cells (GD), monocytic MDSC, regulatory T-cells, NK, and NKT-like cells. DC stimulatory properties were examined by autologous mixed lymphocyte reaction using patient T-cells obtained before DC vaccination (pre-DC) and after min 5 th doses of DCs (post-DC). The stimulation was expressed as % of the division after DC stimulation. Results: ALC was baseline low in 9 of 10 cases and 6 of 10 cases were connected to high (>3) NLR with no significant changes during DC ITx. We observed decrease of NKT-like (p = 0.04) and elevation of GD (p = 0.008) after 13th dose compared to baseline. Post-DC auto-MLR was higher compared to pre-DC in all sarcoma study patients. The median patient T-cell stimulation increased from 8.8% with pre-DC T-cells to 14.6% division with post-DC T-cells. Conclusion: Circulating cell-based immune markers revealed dose-dependent changes in subtle T-cell subsets during the course of DC treatment. Personalized anti-cancer DC-based ITx stimulates a pre-existing immune response against self-tumor antigens. Clinical trial identification: EudraCT: 2014-003388-39. Legal entity responsible for the study: Czech Ministry of Health. Funding: Czech Ministry of Health (Projects LO1413, LM2015090, academic clinical trial). Disclosure: All authors have declared no conflicts of interest.